Retenção de metais pesados em solos agricultáveis do Estado de Goiás - CASTRO, Mara Lucia Lemke de (2009)
The intensification of the use of land for farming has caused great concern, mainly due to the impacts that these activities are causing the environment, particularly with regard to it s contamination by chemicals. The application of chemicals and waste ground and in several, or in plants in order to take agronomically solid waste, improve productivity and increase agricultural production has been growing in the practices of cultivation. The form of improper disposal of waste in the soil, without any control of dose and form of application, and without knowledge of their ability to assimilate the different soil types, possibly predisposing the occurrence of contamination and pollution along the profile these soils and may reach the water table and contaminate groundwater. This work aimed the analysis of the retention of some heavy metals in Ultisol, Oxisol Typic Acrustox, Quartzipsamment and Kandic Oxisol found in savannah soil of the Goiás. Heavy metals in tests were Cadmium (Cd+2), lead (Pb+2), copper (Cu+2), chromium (Cr+3 and Cr+6), nickel (Ni+2) and zinc (Zn+2). The sorption of the heavy metals in soil was evaluated by batch method and described by potential and linear models of the Freundlich isotherm. For the establishment of sorption isotherm were added in 5,0 cm3 of soil and 50,0 cm3 of solution containing the heavy metal being assessed with different concentrations within the limits acceptable soil. The potential and linear sorption isotherm submitted a good adjusted to describe the behavior of adsorption of heavy metals in different classes of soil studied. The detention of heavy metals in descending order was the Ultisol: Cr+3 > Cr+6 > Ni+2 > Zn+2 > Cu+2 > Pb+2 > Cd+2; Oxisol Typic Acrustox: Cr+3 > Cr+6 > Ni+2 > Cu+2 > Cd+2 > Zn+2 > Pb+2; Quartzipsamment: Cr+6 > Cr+3 > Cu+2 > Pb+2 > Ni+2 > Zn+2 > Cd+2; Kandic Oxisol: Cr+3 > Cr+6 > Pb+2 > Cu+2 > Zn+2 > Ni+2 > Cd+2. The Quartzipsamment presented a less retention metal comparison other classes of soil, and therefore more vulnerable to contamination of groundwater.